2020
DOI: 10.1088/1755-1315/616/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Paracoccus Solventivorans sp. as Sulphate Oxidizing Bacteria Isolated from Palm Oil Sludge

Abstract: The emission of hydrogen sulphide (H2S) from industrial processes causesodour nuisance to the surrounding community. Thus, the ability of sulphur oxidizing bacteria could eliminate H2S by changing it into non-odorous elemental sulphur or sulphate. In this study, the isolate bacteria of Paracoccus solventivorans ATCC 700252 demonstrated pH reduction from pH 8 to about pH 5.27 with sulphate content production of454.0 g/ml. The growth of Paracoccus sp. was increased using sulphur as elemental carbon and oxygen as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In another study, SOB (both autotrophs and heterotrophs) were isolated and screened from sulfur water having sulfur oxidation capacity in water (Koul et al, 2018). Recently, many research have been working on the isolation of SOB from different sources with having applications in divergent areas (Borse et al, 2021;Dou et al, 2022;Huynh et al, 2021;Jadhav et al, 2022;Joseph et al, 2021;Nadella et al, 2019;Shinde et al, 2022;Tajarudin et al, 2020;Updegraff et al, 2022;Xie et al, 2021), etc. The initial pH of broth decreased from 8.0 to acidic pH due to the oxidation of sodium thiosulfate to sulfate ions.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In another study, SOB (both autotrophs and heterotrophs) were isolated and screened from sulfur water having sulfur oxidation capacity in water (Koul et al, 2018). Recently, many research have been working on the isolation of SOB from different sources with having applications in divergent areas (Borse et al, 2021;Dou et al, 2022;Huynh et al, 2021;Jadhav et al, 2022;Joseph et al, 2021;Nadella et al, 2019;Shinde et al, 2022;Tajarudin et al, 2020;Updegraff et al, 2022;Xie et al, 2021), etc. The initial pH of broth decreased from 8.0 to acidic pH due to the oxidation of sodium thiosulfate to sulfate ions.…”
Section: Discussionmentioning
confidence: 99%
“…Kambam et al (2015) and Ashraf et al (2018) also screened SOB on the basis of their potential to reduce the pH of the growth medium from 7.8 to ≤5.0 within 15 days of incubation and to oxidize elemental sulfur (S°), and Devi with her team screened rhizobacteria (Indira Devi et al, 2011). Tajarudin et al (2020) also reported the isolation of SOB having the ability to reduce the pH of the medium. In our study, the increase in sulfate production was due to the reaction of BaCl 2 and sulfate in the medium produced by isolates, which results in the formation of barium sulfate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations